O processo judicial sob a perspectiva da teoria da justiça de Axel Honneth - Rezende, Ariadi Sandrini (2017)
The purpose of this dissertation is to investigate whether the judicial process, as it is currently conceived, has the capacity to be a vehicle for execution of social freedom which is investigated by Axel Honneth's theory of justice. In order to do this, it is utilized the book Freedom’s Right, a theoretical milestone of this essay, highlighting the evolution of freedom’s spheres, which originate from juridical sphere, go through the moral and culminate in the social one. Empirical researches were done in the Public Defender's Office of Espírito Santo State. It works as the representative of hyposufficient individuals in proceedings in the court, and it is responsible to diagnosis the level of social freedom in the legal action. There is no certainty if the problem of judicial process, broadens or restricts social freedom. This dissertation will conclude that individuals, who do not participate intersubjectively in the autonomous creation of procedural rules, nor are inserted in social intuitions aimed at solutions of conflicts in society, cannot enjoy social freedom, through heteronomous state justice, in the way introduced by Honneth. This work is due to the current importance given to the philosopher Axel Honneth, mainly because of the emancipatory potential that his philosophy brings from the tradition of the critical theory of Frankfurt school. Analyze the judicial process from the perspective of social freedom, situation that is not explored nationally, allows us to sketch paths to a society of intersubjectively autonomous and emancipated individuals.